PVC/MXene electrospun film triboelectric nanogenerator for efficient mechanical energy harvesting and multifunctional human motion sensing - Lina Liu; Weiqiu Zhu; Haotian Ma; Junyu Zhou (APL Materials)
Wearable devices for human motion monitoring have garnered significant attention in recent years. In this work, the polyvinyl chloride (PVC)/MXene electrospun film-based triboelectric nanogenerator (PM-TENG) was developed for efficient mechanical energy harvesting. Using PVC/MXene as the negative triboelectric material and aluminum foil as the positive material, the PM-TENG exhibits significantly enhanced triboelectric performance, achieving a 325% increase in open-circuit voltage, a 490% increase in short-circuit current, and a 225% increase in transferred charge compared to pure PVC. These enhancements are attributed to MXene’s high conductivity, large surface area, and excellent charge trapping capabilities. The PM-TENG delivers a maximum power output of 4.94 mW at an optimal load resistance of 10 MΩ and boasts a high power density of 4.94 mW/cm2, outperforming existing triboelectric devices. It also demonstrates excellent environmental durability, stability, and multifunctional sensing capabilities, including monitoring physiological signals and biomechanical movements, making it a promising candidate for self-powered wearable sensors, energy harvesting, gesture recognition, and healthcare applications. This research highlights the potential of PM-TENG as high-performance, self-powered systems for energy harvesting and multifunctional sensing, paving the way for advancements in wearable electronics, health monitoring, and sustainable energy solutions.